2017
DOI: 10.1371/journal.pone.0183118
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and glycolytic skeletal muscles show marked differences in gene expression profile in Chinese Qingyuan partridge chickens

Abstract: Oxidative and glycolytic myofibers have different structures and metabolic characteristics and their ratios are important in determining poultry meat quality. However, the molecular mechanisms underlying their differences are unclear. In this study, global gene expression profiling was conducted in oxidative skeletal muscle (obtained from the soleus, or SOL) and glycolytic skeletal muscle (obtained from the extensor digitorum longus, or EDL) of Chinese Qingyuan partridge chickens, using the Agilent Chicken Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, our data showed up-regulation of several genes, such as MYBPC1 and SMPX [127,128], that are more closely associated with slow-twitch oxidative muscle rather than fast-twitch glycolytic muscle. For example, LMOD2 has been alternatively called cardiac leiomodin and its levels in cardiac muscle are directly linked to the length of actin-containing thin filaments due to competition for binding with tropomodulin-1 [129].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data showed up-regulation of several genes, such as MYBPC1 and SMPX [127,128], that are more closely associated with slow-twitch oxidative muscle rather than fast-twitch glycolytic muscle. For example, LMOD2 has been alternatively called cardiac leiomodin and its levels in cardiac muscle are directly linked to the length of actin-containing thin filaments due to competition for binding with tropomodulin-1 [129].…”
Section: Discussionmentioning
confidence: 99%
“…The genes related to muscle growth and fat deposition are PPP3CA, DPYD, and FGGY. Some literature reports that calcineurin (PPP3CA) can promote the dephosphorylation of the nuclear factor of activated T cells (NFAT), allowing it to smoothly enter the nucleus from the cytoplasm, and the target gene of NFAT can participate in skeletal muscle differentiation and Hypertrophic Gene Program (Figure 6(c)) [67, 68]. The DPYD gene is involved in β -alanine metabolism and participated in the modification of lysine, and lysine plays an important role in lipid peroxidation and muscle and muscle bond development (Figure 6(d)).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that PRKAG3 was also related to meat quality [ 46 , 47 ]. Shu et al [ 48 ] found that PRKAG3 expression levels were significantly higher in glycolytic skeletal muscle than in oxidative skeletal muscle by transcriptome sequencing, but a higher content of oxidative (red) fibers in muscles can result in higher meat quality [ 49 ]. This suggested that high expression of the PRKAG3 gene may decrease meat quality.…”
Section: Discussionmentioning
confidence: 99%